2013
DOI: 10.1136/gutjnl-2013-304880
|View full text |Cite
|
Sign up to set email alerts
|

Postcolonoscopy colorectal cancers are preventable: a population-based study

Abstract: In our experience, 86.4% of all PCCRCs could be explained by procedural factors, especially missed lesions. Quality improvements in performance of colonoscopy, with special attention to the detection and resection of proximally located flat precursors, have the potential to prevent PCCRCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
254
4
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 323 publications
(277 citation statements)
references
References 48 publications
14
254
4
5
Order By: Relevance
“…Several studies evaluating interval CRCs found that these cancers can be attributed to incomplete polypectomy in about 10% to 30% of cases 13,20,22,64,65 . Since ADR is essentially geared at assessing detection and not resection, the inadequate quality in these cases would not be reflected by measuring the ADR.…”
Section: Incomplete Adenoma Resectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies evaluating interval CRCs found that these cancers can be attributed to incomplete polypectomy in about 10% to 30% of cases 13,20,22,64,65 . Since ADR is essentially geared at assessing detection and not resection, the inadequate quality in these cases would not be reflected by measuring the ADR.…”
Section: Incomplete Adenoma Resectionmentioning
confidence: 99%
“…In fact, 71% to 86% of interval cancers can be attributed to colonoscopist-related factors, as they represent missed lesions or result from incompletely resected lesions [20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…Recent large population-based studies that evaluated the incidence and risk of interval CRCs at colonoscopy reported that the incidence varies from 2.9% to 7.9% (18)(19)(20)(21)(22)(23). In addition, these studies demonstrated the protective effect of colonoscopy against CRC; however, they also reported that the efficacy of this technique in the proximal colon was limited.…”
Section: Discussionmentioning
confidence: 99%
“…Of the five patients with PCCRC, two were ascribed to missed lesions and three to new lesions. Although it is impossible to evaluate the exact frequency of missed lesions during colonoscopy, recent studies suggest that 23%-58% of PCCRCs are attributable to missed lesions (18,20,24,25). The reasons for missed lesions include incomplete bowel preparation, suboptimal withdrawal time and technique, and differences in the knowledge and training of endoscopists regarding the recognition of subtle-appearing precursor lesions, such as flat and depressed adenoma or sessile serrated adenomas/ polyps (SSA/P) (9).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, up to 20% of all neoplastic lesions, especially small and flat lesions, are still missed during a colonoscopy (3)(4)(5). This unsatisfactorily high overall miss rate remains a concern and is one of the key factors in the development of interval cancer (6). Many common reasons for missing lesions are related to a number of elements of procedural quality such as bowel preparation (7,8), but they also partly result from the highly operator-dependent nature of the procedure (9).…”
Section: Introductionmentioning
confidence: 99%